Unravelling the cellular and molecular pathogenesis of bovine babesiosis: is the sky the limit?. Issue 2 (February 2019) - Suarez, Carlos E.; Alzan, Heba F.; Silva, Marta G.; Rathinasamy, Vignesh; Poole, William A.; Cooke, Brian M.
Highlights: Defining vulnerabilities in the life-cycle of Babesia parasites may lead to designing new control measures for babesiosis. Poorly understood interactions between Babesia parasites and their hosts can be effectively addressed with new technologies. Effective control of babesiosis will require additional extensive integrative research strategies. Abstract: The global impact of bovine babesiosis caused by the tick-borne apicomplexan parasites Babesia bovis, Babesia bigemina and Babesia divergens is vastly underappreciated. These parasites invade and multiply asexually in bovine red blood cells (RBCs), undergo sexual reproduction in their tick vectors ( Rhipicephalus spp. for B. bovis and B. bigemina, and Ixodes ricinus for B. divergens ) and have a trans-ovarial mode of transmission. Babesia parasites can cause acute and persistent infections to adult naïve cattle that can occur without evident clinical signs, but infections caused by B. bovis are associated with more severe disease and increased mortality, and are considered to be the most virulent agent of bovine babesiosis. In addition, babesiosis caused by B. divergens has an important zoonotic potential. The disease caused by B. bovis and B. bigemina can be controlled, at least in part, using therapeutic agents or vaccines comprising live-attenuated parasites, but these methods are limited in terms of their safety, ease of deployability and long-term efficacy, and improved control measures are urgently needed. In addition, expansion of tick habitats due to climate change and other rapidly changing environmental factors complicate efficient control of these parasites. While the ability to cause persistent infections facilitates transmission and persistence of the parasite in endemic regions, it also highlights their capacity to evade the host immune responses. Currently, the mechanisms of immune responses used by infected bovines to survive acute and chronic infections remain poorly understood, warranting further research. Similarly, molecular details on the processes leading to sexual reproduction and the development of tick-stage parasites are lacking, and such tick-specific molecules can be targets for control using alternative transmission blocking vaccines. In this review, we identify and examine key phases in the life-cycle of Babesia parasites, including dependence on a tick vector for transmission, sexual reproduction of the parasite in the midgut of the tick, parasite-dependent invasion and egression of bovine RBCs, the role of the spleen in the clearance of infected RBCs (IRBCs), and age-related disease resistance in cattle, as opportunities for developing improved control measures. The availability of integrated novel research approaches including "omics" (such as genomics, transcriptomics, and proteomics), gene modification, cytoadhesion assays, RBC invasion assays and methods for in vitro induction of sexual-stage parasites will accelerate our understanding of parasite vulnerabilities. Further, producing new knowledge on these vulnerabilities, as well as taking full advantage of existing knowledge, by filling important research gaps should result in the development of next-generation vaccines to control acute disease and parasite transmission. Creative and effective use of current and future technical and computational resources are needed, in the face of the numerous challenges imposed by these highly evolved parasites, for improving the control of this disease. Overall, bovine babesiosis is recognised as a global disease that imposes a serious burden on livestock production and human livelihood, but it largely remains a poorly controlled disease in many areas of the world. Recently, important progress has been made in our understanding of the basic biology and host-parasite interactions of Babesia parasites, yet a good deal of basic and translational research is still needed to achieve effective control of this important disease and to improve animal and human health.